Direct Interactions between the Basolateral Amygdala and Nucleus Accumbens Core Underlie Cocaine-Seeking Behavior by Rats - Di Ciano, Patricia (J Neurosci, 2004)
An insidious feature of drug craving and drug seeking in humans is that it can be induced and maintained by conditioned stimuli after a prolonged drug-free period. Understanding the neural basis of this control over addictive behavior may aid in the development of treatments targeting drug seeking and thereby be beneficial in preventing drug use. In the present study, we used a well established animal model to investigate the functional importance of amygdala-nucleus accumbens interactions in cocaine seeking under the control of drug-associated conditioned reinforcers. To probe the direct neuroanatomical relationship between these structures within a functional corticostriatal loop, we used a neuropharmacological disconnection procedure. Thus, infusing a dopamine receptor antagonist unilaterally into the basolateral amygdala (which had no effect on its own) and an AMPA-kainate (KA) receptor antagonist into the contralateral nucleus accumbens core (which also had no effect on its own) greatly reduced cocaine seeking. We also show that bilateral infusions of the DA receptor antagonist into the amygdala, but not nucleus accumbens, or of the AMPA-KA receptor antagonist in the nucleus accumbens, but not the amygdala, also greatly reduced cocaine seeking. The results of this study demonstrate an amygdala-nucleus accumbens system that critically underlies stimulus-controlled cocaine seeking and indicate possible neurochemical targets for relapse-prevention medication.